Osteopetrosis mimicking juvenile myelomonocytic leukemia. Issue 5 (October 2014) - Hoyoux, Claire; Dresse, Marie Françoise; Forget, Patricia; Piette, Caroline; Rausin, Léon; Villa, Anna; Gothot, Andre; Florkin, Benoit
Abstract A 5‐month‐old boy developed splenomegaly, anemia, thrombocytopenia with elevated white cells, monocytosis and immature granulocytes in the peripheral blood. Bone marrow showed dysplasia without blastosis. Increased colony‐forming unit‐granulocyte–macrophage was found in the peripheral blood, mimicking granulocyte–macrophage colony‐stimulating factor hypersensitivity. These findings fulfilled the diagnosis criteria for juvenile myelomonocytic leukemia (JMML), but no mutations in the CBL, NRAS, KRAS, or PTPN11 genes were detected. In addition to these findings severe hypogammaglobulinemia and elevated alkaline phosphatase were present. Bone X‐ray showed dense and radiopaque bones with a bone‐in‐bone appearance characteristic of infantile malignant osteopetrosis (IMO). Genetic mutation in T‐cell, immune regulator 1 (TCIRG1) was identified, confirming the diagnosis of IMO. Careful differential diagnosis including osteopetrosis, is therefore recommended in patients with clinical features and hematologic findings consistent with JMML.